THE IMPLEMENTATION OF THE COMPILATION OF ISLAMIC LAW ON INHERITANCE LAW: A STUDY IN SLEMAN REGENCY - Juanda, Juanda (IAIN Palangka Raya, 2023)
This paper is the research results on the implementation of Compilation of Islamic Law (CIL) on inheritance law in the Sleman Regency, Special Region of Yogyakarta, in 2019. This study aims to determine the extent of the implementation efforts and uncover some factors hindering the implementation efforts. The type of research used was qualitative, with a qualitative descriptive analysis approach describing the reality under study. Meanwhile, this research